Implementación de Material Didáctico en el área de matemática del segundo año de educación General Básica de la Unidad Educativa Narciso Cerda Maldonado año lectivo 2016-2017 - Ajila Montes, Carla Valeria (2017)
Education is in a constant process of modernization. For this reason, it is a priority to seek alternatives for change and transformation, lack of teaching materials and the effect it causes on learning in the second year of basic education.The objective of this research is to improve the teaching process of students through the implementation of didactic material in the area of mathematics of the second year of basic education of the Educational Unit "Narciso Cerda Maldonado" academic year 2016-2017. The methodology that was used was descriptive and field which allowed me to obtain the data and information necessary to carry out this research, the techniques that were used were the survey, which was addressed to teachers and director of the institution, also Used the observation sheet which was applied to the children of the second year of basic education.This research is important because through the development and application of didactic materials will contribute to improve the teaching-learning process, enabling the teacher to use the resources of the environment to develop the materials needed to deliver their class.The research generated a social impact that allowed to strengthen the knowledge of the teacher, and also contribute positively to society by getting students to become familiar with the teaching materials directly and thus generate meaningful learning. The beneficiaries are the students of the second year of Basic Education and teachers, indirectly will be the entire educational community and parents.